Differential impact of endocrine therapy and chemotherapy on quality of life of breast cancer survivors: a prospective patient-reported outcomes analysis. (8th October 2019) - Ferreira, A R; Di Meglio, A; Pistilli, B; Gbenou, A S; El-Mouhebb, M; Dauchy, S; Charles, C; Joly, F; Everhard, S; Lambertini, M; Coutant, C; Cottu, P; et al.
Abstract: Background: In early breast cancer (BC), there has been a trend to escalate endocrine therapy (ET) and to de-escalate chemotherapy (CT). However, the impact of ET versus CT on the quality of life (QoL) of early BC patients is unknown. Here, we characterize the independent contribution of ET and CT on patient-reported outcomes (PROs) at 2 years after diagnosis. Patients and methods: We prospectively collected PROs in 4262 eligible patients using the European Organization for Research and Treatment of Cancer QLQ-C30/BR23 questionnaires inside CANTO trial (NCT01993498). The primary outcome was the C30 summary score (C30-SumSc) at 2 years after diagnosis. Results: From eligible patients, 37.2% were premenopausal and 62.8% postmenopausal; 81.9% received ET and 52.8% CT. In the overall cohort, QoL worsened by 2 years after diagnosis in multiple functions and symptoms; exceptions included emotional function and future perspective, which improved over time. ET ( P int = 0.004), but not CT ( P int = 0.924), had a persistent negative impact on the C30-SumSc. In addition, ET negatively impacted role and social function, pain, insomnia, systemic therapy side-effects, breast symptoms and further limited emotional function and future perspective recovery. Although CT had no impact on the C30-SumSc at 2-years it was associated with deteriorated physical and cognitive function, dyspnea, financial difficulties, body image and breast symptoms. We found a differential effect of treatment by menopausal status; in premenopausal patients, CT, despite only a non-significant trend for deteriorated C30-SumSc ( P int = 0.100), was more frequently associated with QoL domains deterioration than ET, whereas in postmenopausal patients, ET was more frequently associated with QoL deterioration, namely using the C30-SumSc ( P int = 0.004). Conclusion(s): QoL deterioration persisted at 2 years after diagnosis with different trajectories by treatment received. ET, but not CT, had a major detrimental impact on C30-SumSc, especially in postmenopausal women. These findings highlight the need to properly select patients for adjuvant ET escalation.